Facilely scraping Si nanoparticles@reduced graphene oxide sheets onto nickel foam as binder-free electrodes for lithium ion batteries. (1st March 2016) - Li, Suyuan; Xie, Wenhe; Gu, Lili; Liu, Zhengjiao; Hou, Xiaoyi; Liu, Boli; Wang, Qi; He, Deyan
Abstract: Binder-free electrodes of Si nanoparticles@reducedgrapheneoxidesheets(Si@rGO) for lithium ion batteries were facilely fabricated by scraping the mixture of commercial Si powder, graphene oxide and poly(vinyl pyrrolidone) (PVP) onto nickel foam and following a heat treatment. It was shown that the Si@rGO electrode performs an excellent electrochemical behavior. Even at a current density as high as 4 A/g, a reversible capacity of 792 mAh/g was obtained after 100 cycles. A small amount of PVP additive plays important roles, it not only increases the viscosity of the mixture paint in the coating process, but also improves the conductivity of the overall electrode after carbonization.